Analytical techniques to recognize inclusion complexes formation involving monoterpenes and cyclodextrins: A study case with (–) borneol, a food ingredient. (1st March 2021) - Santana, D.V.S.; Trindade, I.A.S.; Carvalho, Y.M.B.G.; Carvalho-Neto, A.G.; Silva, E.C.D.; Silva-Júnior, E.F.; Leite, R.F.S.; Quintans-Júnior, L.J.; Aquino, T.M.; Serafini, M.R.; Guterres, S.S.; Scotti, L.; et al.
Highlights: Analytical methods to identify when inclusion complexes are formed. Complexes prepared with monoterpenes and different cyclodextrins. Freeze-drying is the best option to form inclusion complexes of borneol. Abstract: Monoterpenes are non-polar secondary metabolites widely used by industry due to their excellent therapeutic, food-ingredient and cosmetic properties. However, their low solubility in water limits their use. In this sense, cyclodextrins (CDs) have been widely used to solve these technological challenges. Thus, this study aims to use (–)-borneol as a monoterpene model to prepare inclusion complexes between β-CD and hydroxypropyl-β-CD (HP-β-CD) through different ways and characterize them in order to choose the best inclusion method to improve physicochemical properties of monoterpenes. To achieve this goal, the samples were prepared by physical mixture (PM), paste complex (PA) and freeze-drying complex (FD) and then, extensively characterized by thermal analysis, Fourier-transform infrared spectroscopy, scanning electron microscopy, size particle, X-ray diffraction and nuclear magnetic resonance. The physicochemical results showed that freeze-drying was more effective to form inclusion complexes between (–)-borneol with both CDs. This research highlights the importance of recognizing the best method to prepare inclusion complexes, including food additives as (–)-borneol, to achieve better results in food preparations.